Lots of spots - Graham, Elspeth (Hong Kong : Oxford University Press, 1999)
Fitting the requirements of the National Literacy Strategy, National Curriculum in England and Wales, English Language 5-14 in Scotland, and Common Curriculum in Northern Ireland, this book guides pupils through the core skills associated with learning to read and write.